Dual descriptions of massive spin-3 particles in D=2+1 via Noether gauge embedment - Mendonça, E. L. [UNESP]; Dalmazi, D. [UNESP] (American Physical Society (APS), 2015)
We present here a relationship among massive self-dual models for spin-3 particles in D=2+1 via the Noether gauge embedment (NGE) procedure. Starting with a first-order model (in derivatives) SSD(1) we have obtained a sequence of four self-dual models SSD(i) where i=1,2,3,4. We demonstrate that the NGE procedure generates the correct action for the auxiliary fields automatically. We obtain the whole action for the fourth-order self-dual model including all the needed auxiliary fields to get rid of the ghosts of the theory.